Protagonist women - Michael MacLennan; Diana Oya Sawyer; Ashleigh Kate Slingsby (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
Protagonist Women highlights examples of women taking the lead in an antagonistic society. The protagonist woman exists on the fault lines of society, championing a now well-established social, cultural and economic revolution. This revolution is aimed primarily at not only garnering women equal rights to men and accounting for historical injustices but carving out a space in society dedicated to tackling the particular challenges faced by women today. In this vein, protagonist women recognise the pluralities of experiences and challenges that exist for women globally. These include biological challenges, those of physical integrity and reproductive health, as well as the challenges and restrictions inflicted by the values and norms of society. This plurality of experiences accounts for the diverse range of issues addressed in this issue of Policy in Focus. [...]
Keywords: 330